Knowledge, Attitude, and Practice Regarding COVID-19 among Residents of Pesantren - Herdayati, Milla; Karniastuti, Juliana (Kesmas, 2021)
Islamic boarding schools (pesantren) run the risk of COVID-19 transmission. The pesantren learning system is generally carried out collectively, with an all-day-long interaction between teachers and students. This paper presented a lesson on controlling COVID-19 outbreak in pesantren through Community Service Activities (CSA). The CSA was designed to empower the pesantren to prevent and control COVID-19 to become a safe place protected from COVID-19 spread. This was a relevant case study in a traditional Islamic boarding school (salafiah) in Lebak District, Banten. The study population (a total of 97 participants) consisted of the pesantren leader, the teachers (“Ustaz/Ustazah”) , and the students, ushered by the community service partners, namely the Sub-district Public Health Center and COVID-19 Task Force. This study showed that controlling COVID-19 in pesantren requires the leaders’ commitment to establishing an internal COVID-19 Task Force and partnerships with community stakeholders. Health literacy needs to be improved, especially by implementing health protocols and information on clean and healthy behavior. There are obstacles in handling COVID-19, especially related to social distancing, infrastruc-ture, and funding. This study recommends the empowerment of pesantren residents related to health literacy. It is necessary to make people realize that COVID-19 is everyone’s responsibility. The Government should pay serious attention to pesantren as boarding educational institutions with a high level of in-teraction and prevent them from becoming clusters of COVID-19 spread.